2010
DOI: 10.1056/nejmoa0902045
|View full text |Cite
|
Sign up to set email alerts
|

Stent Graft versus Balloon Angioplasty for Failing Dialysis-Access Grafts

Abstract: In this study, percutaneous revision of venous anastomotic stenosis in patients with a prosthetic hemodialysis graft was improved with the use of a stent graft, which appears to provide longer-term and superior patency and freedom from repeat interventions than standard balloon angioplasty. (ClinicalTrials.gov number, NCT00678249.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
114
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(126 citation statements)
references
References 36 publications
8
114
0
4
Order By: Relevance
“…Sixmonth access circuit patency rates among AVFs and AVGs in our study were observed at 47.1 and 34.9 %, respectively. Prior published studies reported 6-month access primary patency rates between 40 and 57 % among AVFs [6,12,14] and 20 and 40 % among AVGs [5,6,15]. Our findings are comparable to these aforementioned studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Sixmonth access circuit patency rates among AVFs and AVGs in our study were observed at 47.1 and 34.9 %, respectively. Prior published studies reported 6-month access primary patency rates between 40 and 57 % among AVFs [6,12,14] and 20 and 40 % among AVGs [5,6,15]. Our findings are comparable to these aforementioned studies.…”
Section: Discussionsupporting
confidence: 89%
“…Although the small sample size of our population may limit interpretation of significance, a prior randomized prospective study with larger sample size (n = 93) demonstrated similar results [5].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, short-term restenosis leading to increased re-intervention and access thrombosis events has limited its clinical efficacy [1]. In 2010, results from a multi-center randomized trial reported that self-expandable stent graft deployment is a valid alternative that may outweigh traditional BA for the treatment of venous juxta-anastomotic stenosis of AVGs [3].…”
Section: Introductionmentioning
confidence: 99%